Pengajian Qiraat di Fakulti Pengajian Quran dan Sunnah, USIM: Analisis Terhadap Tahap Kefahaman Qiraat - Zainora Daud; Hayati Hussin; Mohd Shamsul Hakim Abd Samad; Khairul Anuar Mohamad (Universiti Sains Islam Malaysia, 2024)
Qiraat Studies is a relational knowledge that discusses ways of Quranic recitation with the agreed and disputed recital based on the authentic sanad narrated by the qiraat scholars including hadhaf, ithbat, taḥrik, taskin, al-fasl, al-wasl and in any similar manners through talaqqi and musyafahah. The findings from the previous studies showed that the qiraat capability among the students is still at a moderate level, with some constraints within themselves as well as the ABM usage in the classroom. The Faculty of Quranic and Sunnah Studies, USIM is the first Public University faculty in Malaysia to introduce the Bachelor of Quran and Sunnah Studies (With Honors) program and has offered the subject of Qiraat and Hafazan as a compulsory course and Qiraat Amali II as an elective subject in this program. While Qiraat Amali I and Qiraat Amali II are the compulsory courses in the Bachelor of Quran Studies with Multimedia (Hons). The objective of this research is to identify students' background and to study the level of students' understanding of Qiraat. The research design used was a quantitative method using a survey method. The level of Alpha Cronbach's reliability value obtained for all instruments in the questionnaire was high (> 0.8). A total of 201 respondents answered the questionnaires distributed among the two Bachelor Degree programs namely the Quran and Sunnah and the Quran with Multimedia based on the Proportionate Stratified Random Sampling. The findings show that the level of understanding of students in qiraat studies is good but still requires continuous improvement so that students would have a high interest and passion in the field of qiraat studies.